Four new phenolic glycosides from Baoyuan decoction - Xiaoli Ma; Xiaoyu Guo; Mingbo Zhao; Pengfei Tu; Yong Jiang (Elsevier, 2017)
Four new phenolic glycosides, including two flavonoid glycosides (1 and 2) and two lignan glycosides (3 and 4), were isolated from the traditional Chinese medicine formula, Baoyuan decoction. Their structures were established by detailed analysis of the NMR and HR-ESI-MS spectroscopic data and their absolute configurations were determined by the experimental electronic circular dichroism data as well as chemical methods. Furthermore, the sources of the four new compounds were determined by the UPLC-Qtrap-MS method, which proved that 1 and 2 are originated from Glycyrrhiza uralensis, and 3 and 4 are from Cinnamomum cassia.